Pengembangan Aplikasi Katalog dan Pemesanan Produk Kebutuhan Dapur Berbasis Android menggunakan Metode Mobile-D - Arya Yudha Mahendra; Adam Hendra Brata; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Each year, Internet users are growth rapidly. Those are also supported with the growth of the internet supporting device user. Mobile application device is a major booster on the increases of internet users in Indonesia, it's reaches 47% of the total population. From those data, about 46% use internet to visit online market place. Android becomes the most popular operating systems among others, with 77% of mobile device users use it. It is certainly very useful for residents of Malang City which 34% of population are sellers or merchants. Therefore, a supporting applications that facilitate transaction processes is necessary both for the sellers and consumers. This research will explain application development that can facilate transaction between sellers and consumers by emphasizing the ease of operation. The mobile-d method is adopted because it has obtained a level 2 CMMI certificate and has a development flow that is suitable for off-site customer. In addition, Mobile-d is iterative to meet changing of needs which are suitable for exploring the immediate needs of end-user users. To collect data, reseacher use interviews and questionnaires. Based on the results of research conducted, the assessment of users of the application has an average score SUS value of 84,37 on the consumer side and 72,5 on the seller side. These numbers, prove if the app has a usefulness, ease, and purity is good enough for the user.